2019
DOI: 10.1016/j.bbmt.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The Dilemma of Conditioning Intensity: When Does Myeloablative Conditioning Improve Outcomes for Allogeneic Hematopoietic Cell Transplantation

Abstract: The impact of conditioning intensity on different disease risk index (DRI) groups has not been evaluated. We retrospectively analyzed acute myelogenous leukemia (AML)/myelodysplastic syndrome (MDS) hematopoietic cell transplantation (HCT) recipients in 2 groups based on DRI, to assess the impact of conditioning intensity on overall survival (OS), disease free survival (DFS), relapse, and nonrelapse mortality (NRM). A total of 380 patients with either high/very high (n = 148) or low/intermediate DRI (n = 232) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…As previously noted, all patients that received the ATG + PTCy combination also underwent RIC, which generally is considered to be associated with an increased relapse risk, at least in the non-high-risk disease groups [8]. However, various studies have demonstrated that while disease risk at diagnosis is a significant factor in predicting AML relapse after transplantation, conditioning intensity does not seem to play a role in the high-risk disease group [7, 8, 23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously noted, all patients that received the ATG + PTCy combination also underwent RIC, which generally is considered to be associated with an increased relapse risk, at least in the non-high-risk disease groups [8]. However, various studies have demonstrated that while disease risk at diagnosis is a significant factor in predicting AML relapse after transplantation, conditioning intensity does not seem to play a role in the high-risk disease group [7, 8, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Conditioning intensity plays a significant role in post-transplant relapse risk, with reduced-intensity regimens being associated with increased relapse rates. For high-risk myeloid malignancies, however, such as those with a monosomal karyotype, the relapse risk does not seem to be overcome by increasing the conditioning intensity [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…One analysis evaluated 380 AML/MDS patients with either high/very high or low/intermediate DRI. 55 Among patients with high/very high DRI, there was no difference in outcome between the RIC and MAC groups. For low/intermediate risk DRI, recipients of MAC showed better 3-year overall survival (69% vs .…”
Section: Factors Which May Be Helpful In the Decision Process: Balance Between The Risk Of Relapse And Non-relapse Mortalitymentioning
confidence: 93%
“…Despite known off-target impairment of beneficial graft-versus-leukemia (GVL) and limited tolerance induction (3), calcineurin inhibitors have been included in GVHD prophylaxis and treatment for more than 3 decades (4)(5)(6). While advances in donor and graft selection (7,8), recipient comorbidity assessment (9,10), and conditioning regimens have improved allo-HCT outcomes (11,12), the use of calcineurin inhibitors remains prevalent in GVHD prevention (1). In particular, calcineurin inhibitors are still incorporated in the popular use of posttransplant cyclophosphamide-based regimens as GVHD prophylaxis (13).…”
Section: Introductionmentioning
confidence: 99%